Scarification in Acetic Acid, Hot Water, and Cold Sand Stratification to Improve Carob (Ceratonia Siliqua L.) Seed Germination - Khalid Khalil; Younis Suleman (Tikrit Journal for Agricultural Sciences, 2022)
This study was carried out to determine the effects of acetic acid, hot water, and cold sand stratification scarification at different periods on seed germination of carob (Ceratonia siliqua L.) in Salah Alden province. The seeds were collected from Kirkuk province area on September 2016. Carob seeds stratified and not stratified treated by soaking in glacial acetic acid for 20, 40, 60, and 120 min. at lab temperature (25oC). Hot water (100oC) also used for soaking the seeds for 20, 40, 60, and 120 min. Experimental design of Randomized Complete Block Design (RCBD) with 3 replicates, and 10 seeds per each treatment per each replicate were used and the results were compared to non-treated seeds. After soaking the seeds in acetic acid and hot water, they washed thoroughly and sowed in black polyethylene grow bags. The soil used was loamy with added organic matter. After 7 months, data recorded on the germination percent and growth features including plant height, leaf area, total chlorophyll, root length, fresh and dry weight of vegetative parts, nitrogen, phosphorous, and potassium percentages in the plant. The results showed that the treatment with hot water for 60 minutes achieved the highest percent of germination (96.67%), highest leaf area 12.86 cm2, highest root dry weight (0.14 gm.), and nitrogen percent of 5.52%. The treatment for 40 minutes with hot water gave the highest fresh weight of vegetative parts was 18.6 gm. and root fresh weight (7.05 gm.). The treatment with hot water for 120 minutes achieved the highest percent of phosphorous and potassium (0.49% and 2.07% respectively).